SELESAIAN ANALITIS TERHADAP PROBLEM DISPATCH EKONOMI DALAM PENERAPANNYA SEBAGAI BASIS PELELANGAN ENERGI LISTRIK - Rajab, Abdul
Abstract: Indonesia Electric power system is on going restructuring process toward a competitive power market. In the competitive environment, generators must be operated efeciently to compete for the right to suply demand in a given time trough the auction mechanism. This paper present an auctioli mechanism based on \"Analytical solution to the economic dispatch problem\". The solution is unique and can be found exactly without the need of numerical iterative optimization algorithms. The problems that occur when identical units prevent Lagrangian Relaxation from finding optimal solution, are not present. The modification made in this paper can guarantee that the solution found is the cheapest one. That is, the use of dinamic programming to solve unit commitment problem. Finally, we find out the exact result by analytical solution.